Total asset prediction of the large Indonesian bank using adaptive artificial neural network back-propagation - ., Fariyanti; ., Iskandar; Malani, Rheo; Suprapty, Bedi (International Journal of Engineering and Technology, 2018)
The bank is a type of company that acts as the executor of monetary policy and as a guarantor of the stability of the financial system of a country. Total assets are an important aspect for a bank to generate net income. Return on Assets (ROA) is a profitability ratio to measure the ability of a bank in generating profits with all investments owned. This study predicts the total assets of the largest banks in Indonesia, referring to the Indonesia Stock Exchange data from 2005 to 2016. The time series data model used is Autoregressive (AR) model and Multi Input Single Output (MISO) Autoregressive with exogenous input (ARX) model. Adaptive Artificial Neural Network Back-propagation (Adaptive ANN-BP) is used as an approximation model of both models.Â Â
Keywords: net total assets; net income; ROA; AR model; MISO-ARX model; Adaptive NNBP